PEMANFAATAN FRAMEWORK TOGAF UNTUK PERENCANAAN SISTEM INFORMASI MANAJEMEN ASET DAN LOGISTIK DI IBI DARMAJAYA BANDAR LAMPUNG (STUDI KASUS : IBI DARMAJAYA BANDAR LAMPUNG) - Melda Agarina (IIB Darmajaya, 2015)
Bureau of Asset Management and Logistics has the main task that covers the planning, procurement, management, maintenance and security infrastructure in the IBI Darmajaya. This bureau has been utilize the information technology, especially in the Logistics Section already has an application that is designed specifically to facilitate the work that is associated with procurement. It is not quite ideal, given the complexity of the existing work in the Bureau of Asset Management and Logistics. Integration and sharing of data between relevant section in the Bureau of Asset Management and Logistics can not be done well. The method in this study used 5 stages of ADM TOGAF in the process of planning the development of this information system. Based on the results of the implementation of the TOGAF ADM framework, information systems architecture consisting of 19 proposals generated application that will be used to support the work of the Bureau of Asset Management and Logistics IBI Darmajaya. The results of this research is a blueprint for asset management information system and the integrated logistics so we expect that the resulting of information system to facilitate the implementation of existing business processes and meet the different needs in that area.Keywords: Asset Management , Integration , Data Sharing , TOGAF ADM